Great inventions that changed the world - Wei, James 1930- (Wiley, 2012)
"Written by one of the world's great engineers, this book provides the curious with an explanation of how inventions have developed from human needs and desires. Chapters discuss the impacts of inventions in our work, personal lives, societies, and the environment. The text also outlines what steps we need to take to ensure continued success of new inventions, and how to mange them wisely. Based on a Princeton University course for a general audience, this book lays out a means for understanding yesterday and today's inventions, and paves the way for tomorrow's innovations. This book is designed for a general audience, similar to those who would read Scientific American. The book describes how inventions arise from human needs instead of when the inventions were made or what technologies were involved. Chapter 1 introduces the world of inventions, and the common features of major inventions and inventors. Chapters 2 through 8 describe human needs and desires, and how inventions support them"--Provided by publisher.